conceptual field stoichiometry of chemical reactions. part i: didactic transposition in a college course (Revista Electrónica REDINE, 2018)
Teaching chemistry, it involves: besides speaking their language, develop schemes that approach the scientific view of the discipline. Advances in teaching chemistry lead to reconsider the teaching activity around how to design, to instruct and evaluate the pedagogical action. This paper proposes a series of actions that let to design sequences teaching concerning to stoichiometry field. It includes a series of tasks to define and explain the content. Three tasks identified a Take into account in the definition of the concept from science field; scientific analysis, didactic analysis and the analysis of situations. In this regard, it is considered necessary to produce a link between the teaching of chemistry and epistemology, in order to sequence activities class. The focus of this study is channeled to the conceptual, since, highlight the development of ideas, concepts and theorems of the student. The intention was coupling the teaching job with the prospect of the theory of Vergnaud. From this task are drawn several positive conclusions, recommending apply the methodology, as the teaching propose in college chemistry courses.
Keywords: stoichiometry; conceptual fields; didactic transposition